2018
DOI: 10.1061/(asce)up.1943-5444.0000469
|View full text |Cite
|
Sign up to set email alerts
|

Multiagent Spatial Simulation of Autonomous Taxis for Urban Commute: Travel Economics and Environmental Impacts

Abstract: With the likelihood of autonomous vehicle technologies in public transport and taxi systems prior to privately-owned vehicles increasing, their actual impact on commuting in realworld road networks is insufficiently studied. In this study, an agent-based model is developed to simulate how commuters travel by autonomous taxis (aTaxis) in real-world road networks. The model evaluates the travel costs and environmental implications of substituting conventional personal vehicle travel with aTaxi travel. The propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 37 publications
1
40
0
1
Order By: Relevance
“…Studies showed that one SAV could feasibly replace anywhere from 5 to 14 private vehicles. 26,29,31,88,89 The replacement rate of SAEVs depends on battery capacity and charger availability. 33,87 SAEVs have lower replacement rates than SAVs because SAEVs need to be charged, a process that takes longer than conventional refueling.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Studies showed that one SAV could feasibly replace anywhere from 5 to 14 private vehicles. 26,29,31,88,89 The replacement rate of SAEVs depends on battery capacity and charger availability. 33,87 SAEVs have lower replacement rates than SAVs because SAEVs need to be charged, a process that takes longer than conventional refueling.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Unlike a lot of previously published research studies only evaluating GHG production by the operation of electric vehicles from a regional perspective [45][46][47], some studies also take into account GHG production from the perspective of electricity generation [48,49]. The submitted manuscript takes into account the share of the primary sources in electricity production and the efficiency of electricity production and distribution as well.…”
Section: Introductionmentioning
confidence: 99%
“…While recent research on the energy use impacts of vehicle automation does consider the impact of time cost changes (for example, Wadud et al [5]), it tends to borrow fuel and time cost elasticities that are estimated elsewhere, in isolation from each other, and without the aim of developing CAV-specific predictions. Most studies focus on how changes in mobility -especially changes in the vehicle-level energy efficiency of CAVsaffect energy use, holding travel demand constant (for instance, [21][22][23][24]). The assumption of fixed demand almost certainly leads to overestimation of the environmental benefits of this technology [2].…”
Section: Introductionmentioning
confidence: 99%